Using an Extension of The Theory of Planned Behavior to Explore University Students' Intention to Pursue Career in The Hospitality Industry - Hsieh, Tsai-Chih (Advances in Social Sciences Research Journal, 2023)
The hospitality industry has always been noticed as a labor demanding field, and therefore manpower training is very critical to the hospitality industry. However, even when hospitality-related universities and technology schools are growing, there is still the dilemma of lack of manpower needs in the industry. Therefore, the main purpose of this research is to use the extended version of the planning behavior to add emotional intelligence and confront mechanisms to analyze the intention of university or science and technology students to invest in the hospitality industry in the future. This study conducted a survey of current and completed internship students in a science and technology university. A total of 302 valid questionnaires were collected and analyzed by structural equation modeling. The results found that the original planning behavior theory is not good at predicting behavioral intentions. In other words, whether students are involved in the hospitality industry is mostly based on emotional elements.